The construction of modern science : - Westfall, Richard S. (Wiley, 1971)
This introduction to the history of science in the seventeenth century examines the so-called 'scientific revolution' in terms of the interplay between two major themes. The Platonic-Pythagorean tradition looked on nature in geometric terms with the conviction that the cosmos was constructed according to the principles of mathematical order, while the mechanical philosophy conceived of nature as a huge machine and sought to explain the hidden mechanisms behind phenomena. Pursuing different goals, these two movements of thought tended to conflict with each other, and more than the obviously mathematical sciences were affected - the influence spread as far as chemistry and the life sciences. As this book demonstrates, the full fruition of the scientific revolution required a resolution of the tension between the two dominant trends.